The complete mitochondrial genome of Cryptalaus larvatus (Coleoptera: Elateridae). Issue 2 (2nd April 2020) - Li, Yechen; Wan, Yi; He, Huan; Guo, Yajie; Jiang, Linghan; Huang, Chenyan; Zhang, Feiping
Abstract: In this study, we sequenced the first complete mitochondrial genome of Cryptalaus larvatus . The complete mitochondrial genome of C. larvatus was 15, 876 bp with 29.80% GC containing 13 protein-coding genes, 22 transfer RNA (tRNA), two ribosomal RNA (rRNA), as well as and an AT-rich region. Phylogenetic analysis showed that the C. larvatus, Pyrophprus divergens, Ignelater luminosus, Hapsodrilus ignifer, and Dicronychus cinereus were clustered together. This study provides important information for the identification of this species and the study of genetic evolution with other species of Elateridae.